“Bend so you don’t break!” A longitudinal moderated mediation study on human resources management practices, humility, psychological well-being, and job performance - Parent-Lamarche, Annick; Dextras-Gauthier, Julie (Frontiers in Psychology, 2024)
This study aims to examine the mediating role of psychological well-being in the relationships between human resources management practices and job performance. Also, this study aims to assess the moderating role of humility on these relationships. Multiple regression, mediation, and moderation analyses were conducted with MPlus software on a sample of 569 workers who filled out a questionnaire at both Time 1 and Time 2. Both data collections took place between April 20, 2022, and May 2, 2022, for Time 1, and between June 20, 2022, and July 3, 2022, for Time 2. Data were collected through the Leger Opinion (LEO) online panel, with respondents required to be workers. We found that psychological well-being at T1 did not play a mediating role between human resources management practices at T1 and job performance at T2. Also, humility did not moderate the relationships between human resources management practices at T1 and psychological well-being at T1 but did significantly moderate the longitudinal relationships between human resources management practices at T1 (i.e., dotation, formation, career management, autonomy, occupational health and safety, diversity management, indirect compensation, flexibility, performance management), and job performance at T2. For all significant interactions, the results indicated that when humility was high, the longitudinal effect of good human resources management practices led to high in-role job performance.